Ethnomycological Notes on Haploporus odorus and other Polypores in Northern Fennoscandia - Svanberg,, Ingvar (Journal of Northern Studies, 2018)
This study focuses on the use of polypores in northern Fennoscandia, especially the now rare Haploporus odorus, which was once used by Sami and Swedish peasantry in the north. However, other taxa that were culturally salient are also discussed. Polypores have been used for health-related, technical and other purposes. The use of some of the taxa, such as Fomes fomentarius and Fomitopsis betulina, has been widely known over Eurasia and beyond, while Haploporus odorus has been utilized only by the North American Plains tribes and in northern Scandinavia. From cultural historical information, ethnographical data and observations reported in travelogues, the ethnomycological significance of five bracket fungi species in northern Fennoscandia has been identified.